Effect of breastfeeding versus infant formula on iron status of infants with beta thalassemia major - Usama Roshdy El Safy; Manar Mohamed Fathy; Tamer Hasan Hassan; Marwa Zakaria; Mohamed Abdel Kader Al Malky; Mohamed Arafa; Hany El Sayed; Ashgan Al Ghobashy; Boshra Zaho; Attia Abdel Wahab; Mohamed Hosam Mourad (BMC, 2017)
Abstract Background Thalassemia major or Cooley's anemia is the most severe form of beta thalassemia in which the complete lack of beta protein in the hemoglobin causes a life-threatening anemia requiring regular blood transfusions and extensive ongoing medical care. These extensive, lifelong blood transfusions lead to iron-overload that must be treated with chelation therapy to prevent early death from organ failure. We compared serum iron and ferritin levels amongst infants aged up to one year with beta thalassemia major according to their feeding types, including exclusively breastfed, exclusively formula fed and combined (both breast and formula) fed types. Methods Sixty out of 176 screened infants with transfusion dependant beta thalassemia major were recruited from the outpatient clinic of thalassemia at Zagazig University Hospital in Egypt, between 2007 and 2014. Patients were classified into three groups (20 patients per group) according to type of feeding. Group 1: exclusive breastfeeding, around 6-8 feeds per day; group 2: exclusive infant formula feeding, 120-150 ml of formula per kilogram of body weight per day divided into 6-8 feeds and group 3: combined breastfeeding and formula per day. Results Serum iron and ferritin levels were lower in group 1 compared to groups 2 and 3. The mean serum iron for group 1 was 73, 87 and 96 ug/dl at 6, 9 and 12 months respectively, while that for group 2 was 85, 99 and 112 ug/dl at 6, 9 and 12 months respectively and for group 3 was 78, 92 and 99 ug/dl at 6, 9 and 12 months respectively. The mean serum ferritin for group 1 was 283, 327 and 497 ng/ml at 6, 9 and 12 months respectively, while that for group 2 was 310, 389 and 591 ng/ml at 6, 9 and 12 months respectively and for group 3 was 291, 345 and 515 ng/ml at 6, 9 and 12 months respectively. The differences were not statistically significant. Conclusions Breastfed infants with beta thalassemia major may accumulate less iron than infants fed iron fortified formula anticipating later onset of iron overload in the breastfed infants. Larger studies are needed to support these findings.